ANALISIS LEARNING OBSTACLES MAHASISWA DALAM MEMPELAJARI MATERI KOMBINATORIAL - Astuti, Robia (Edumath, 2017)
The purpose of this research is in-depth analysis of the obstacles to student learning based on various types of errors in solving combinatorial. Subjects were students of sixth semester the number of students who have been awarded 5 combinatorial materials. Sampling technique used is purposive sampling. Combinatorial tests used to analyze student errors relating to the concepts, principles, and operations. Data were analyzed using triangulation techniques to test the credibility of the data is done by checking the data to the same source with different techniques. Data obtained from the interviews will be checked with data based on the test results. The results of the study concluded that some of the errors of students in solving combinatorial, such as: errors in the received information to restate a concept; errors related to the concept of classifying objects according to certain properties; errors related to the calculation and procedures; error in applying the concept or problem-solving algorithm.